Road safety - the experience of the Transport Accident Commission in Victoria, Australia - Samantha Cockfield (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
The Transport Accident Commission of Victoria (TAC) was established, and is governed by, the Transport Accident Act 1986. The TAC administers a comprehensive no-fault compensation scheme for Victorians who are injured or die as a result of a transport accident. The Act also provides the TAC with a role in accident prevention and reducing the cost of transport accidents to the Victorian Community. (...)
Keywords: 330